209k views
5 votes
3(2x - 1) + 5 = 6(x + 1)



HELP!!!

User David Ford
by
5.0k points

2 Answers

0 votes

Answer:

no solution

Explanation:

Given

3(2x - 1) + 5 = 6(x + 1) ← distribute parenthesis on both sides

6x - 3 + 5 = 6x + 6 , that is

6x + 2 = 6x + 6 ( subtract 2 from both sides )

6x = 6x + 4 ( subtract 6x from both sides )

0 = 4 ← not possible

This indicates the equation has no solution

User Musiq
by
4.6k points
6 votes

Answer:

No Solution

Explanation:

I have tried it a few times and there seems to be no solution. x can't be solved for.

User EverTheLearner
by
4.2k points